2015
DOI: 10.1002/jhm.2297
|View full text |Cite
|
Sign up to set email alerts
|

Changes in patient satisfaction related to hospital renovation: Experience with a new clinical building

Abstract: IMPORTANCE There is an increasing trend toward designing hospitals with patient‐centered features like reduced noise, improved natural light, visitor friendly facilities, well‐decorated rooms, and hotel‐like amenities. It has also been suggested that because patients cannot reliably distinguish positive experiences with the physical environment from positive experience with care, an improved hospital environment leads to higher satisfaction with physicians, nursing, food service, housekeeping, and higher overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 22 publications
(42 reference statements)
3
50
2
2
Order By: Relevance
“…One of these was a small randomised controlled trial, finding that the use of therapy dogs prior to physical therapy sessions for orthopaedic patients improved Pain Management, Communication with Nurses and Overall Hospital Rating 14. Two studies with pre-post assessment found that constructing a new hospital building improved Cleanliness of Hospital Environment, but did not impact other domains16 and that physician education and real-time feedback of patient satisfaction via an information technology intervention improved Communication with Doctors and Recommend the Hospital domains 12. Another pre-post assessment of a pharmacy team intervention found significant improvement for Communication about Medicine domain,19 while an observational study assessing an intervention consisting of communication training for attending physicians found improvement in a single item of Communication with Doctors 17.…”
Section: Resultsmentioning
confidence: 99%
“…One of these was a small randomised controlled trial, finding that the use of therapy dogs prior to physical therapy sessions for orthopaedic patients improved Pain Management, Communication with Nurses and Overall Hospital Rating 14. Two studies with pre-post assessment found that constructing a new hospital building improved Cleanliness of Hospital Environment, but did not impact other domains16 and that physician education and real-time feedback of patient satisfaction via an information technology intervention improved Communication with Doctors and Recommend the Hospital domains 12. Another pre-post assessment of a pharmacy team intervention found significant improvement for Communication about Medicine domain,19 while an observational study assessing an intervention consisting of communication training for attending physicians found improvement in a single item of Communication with Doctors 17.…”
Section: Resultsmentioning
confidence: 99%
“…, Siddiqui et al . ). Smart textile medical devices are perceived as comfortable, intimate and cozy, which in turn fit in with the broader project of homelike hospitals.…”
Section: Resultsmentioning
confidence: 97%
“…, Siddiqui et al . ). This is part of a broader move to conceptualise patients as consumers, and it is often done under the banner of patient‐centred care (Bromley ).…”
Section: The Contemporary Contours Of Medicalisationmentioning
confidence: 97%
See 1 more Smart Citation
“…Although some portion of satisfaction would likely be attributable to a honeymoon effect of the state-of-the-art environment and reestablishment of a health care facility in the community, we note that recent data from a substantial study indicate that patients do discriminate the quality of clinical care apart from the features of comfortable new surroundings. 65 …”
Section: Resultsmentioning
confidence: 99%